Internal Control over Financial Reporting (ICoFR) in Indonesia: Regulatory Development, Implementation Challenges, and Organizational Readiness Framework - Adrian Adrian; Oktavia Marpaung; Verdi Yasin; Kuncoro Wibowo (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Reliable financial reporting is essential for investor confidence, corporate governance, and sustainable organizational performance. The increasing complexity of business operations and regulatory expectations has heightened the importance of Internal Control over Financial Reporting (ICoFR). Indonesia recently introduced a mandatory ICoFR framework through Financial Services Authority Regulation (POJK) No. 15 of 2024 and the Minister of State-Owned Enterprises Decree No. SK-5/DKU.MBU/11/2024. This study examines the development of ICoFR regulations in Indonesia, identifies key implementation challenges, and proposes an Integrated Organizational Readiness Framework for Internal Control over Financial Reporting (IORF-ICoFR). Using an integrative literature review and regulatory analysis, the study synthesizes international governance frameworks, Indonesian regulations, and professional implementation guidance. The findings indicate that effective ICoFR implementation depends not only on regulatory compliance but also on organizational readiness, including governance, leadership commitment, human capital, business process maturity, technology governance, risk management integration, and continuous monitoring. The proposed framework provides a practical reference for organizations seeking to strengthen internal controls and enhance the reliability of financial reporting. This study contributes to the literature by integrating regulatory and organizational readiness perspectives within the Indonesian context and offers practical implications for regulators, financial institutions, state-owned enterprises, audit committees, internal auditors, and corporate management.